Modeling the Effects of Directed Contact Diathermy on Biological Tissue - H. Y. Navitskaya; P. V. Kamlach; D. V. Likhacheuski; V. M. Bandaryk; M. V. Davydov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Directional contact diathermy is one of the most promising methods of physiotherapy. To study it, biophysical modeling of the effect of capacitive-resistive energy transfer (TEKAR therapy, or TR therapy) on biological tissue was carried out in the COMSOL Multiphysics environment using the finite difference method. A model of a biological object exposed to TR therapy was created. The visualization of the distribution of temperature and electric potential in the volume of the model is carried out. The dependence of the heating intensity on the frequency of alternating current is determined. The dynamics of temperature changes in each layer of biological tissue is shown.